First records of Chrysomelidae (Insecta, Coleoptera) on blueberries in Argentina: new associations between native chrysomelids and an exotic crop - Cabrera, Nora Clara (2012)
The blueberry, Vaccinium corymbosum L. (Ericaceae), is a shrub native to the northern Hemisphere introduced in Argentina, where it occupies small cultivated areas mainly in the provinces of Buenos Aires, Entre Ríos and Tucumán. At present, little is known about insects associated with this crop in Argentina. The aim of this study was to identify the species of Chrysomelidae present in blueberry crops in different regions of Argentina, and to present new chrysomelids-blueberry associations. Identification diagnosis, geographical distribution, association with other plants and aspects of their biology is given for each species. Seven species of crop-damaging Chrysomelidae were recorded in blueberry crops of Buenos Aires and Entre Rios. They belong to the subfamilies Galerucinae: Diabrotica speciosa (Germar), Disonychodes exclamationis (Boheman), Caeporisstigmula Germar, and Cacoscelis melanoptera Germar; Eumolpinae: Percolaspis varia (Lefèvre), and Spintherophyta semiaurata (Klug); and Cryptocephalinae: Lexiphanes coenobita Suffrian.